Genetic divergence analysis of deshi jute (Corchorus capsularis) based on fibre yield and its attributing traits (Progressive Agriculture, 2020)
Commercially important natural fibres considered as fiber of the future are obtained from the bark of two jute species (Corchorus capsularis L. and Corchorus olitorius L.), and they are cultivated in different south-east Asian countries including India and Bangladesh. Unfortunately, they are characterized by narrow genetic variability for adaptability to not only various agronomic environments, but also fibre yield, quality and susceptibility to diseases and pests. Therefore, research on genetic divergence in this crop is very important in formulating a successful breeding program for evolving cultivars superior in both yield and quality to cater to the increasing demand of value added jute products in the domestic and international markets. In our study, which was conducted at the Central Jute Research Experiment Station of Bangladesh Jute Research Institute (BJRI), during Kharif seasons of 2015.44 accessions of deshi jute (Corchorus capsularis L.) originated from different countries and two varieties CVL-1 and CVE-3 (developed from Bangladesh Jute Research Institute) as check were investigated to study the genetic variability, genetic diversity and degree of association of different component characters related to fiber yield. The seeds of experimental plant materials were grown in Randomized Complete Block Design with three replications. Statistical analysis was run to find out the genotypic and phenotypic variances, correlations and cluster analysis for fibre yield related traits namely technical height (m), leaf angle (dg), leaf length (cm), leaf width (cm), petiole length (cm), node no., base diameter (mm), middle diameter (mm), top diameter (mm), core diameter (mm), dry fibre weight (g), dry stick weight (g). Highly significant differences were observed among the genotypes for all the characters. Substantial amounts of genotypic variance were also obtained for all characters. Fibre weight was significantly and positively correlated with node no., base diameter, middle diameter, top diameter and core diameter. The clustering pattern revealed considerable amount of genetic diversity observed among the genotypes studied here and the accessions were grouped into five clusters. From two years’ evaluation it was revealed that the accessions 2512, 2445, 2749 and 2533performed better in most of the cases than the control varieties CVL-1 and CVE-3. These accessions may be used as parents for future variety development program.Progressive Agriculture 31 (1): 26-35, 2020